Analytical study of the curve of static bending test for wood specimens - Almeida, Tiago Hendrigo de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
The NBR 7190:1997 “Design of Timber Structures” provides the procedure for several mechanical tests, and among them, the Static bending test for Modulus of Elasticity (Em) and Conventional Value of Strength (fm) determinations. It is common to characterize wood batches with a small number of specimens, what makes it difficult to perform an estimative test for rupture determination, and afterwards, to carry out the loading cycle for Em estimation. In these cases, instead of Force parameters, Deflection parameters are used for the loading cycle. This paper aims to identify a pattern between Force and Deflection parameters by investigating the Force vs. Deflection curve of the static bending test of wood specimens. According to results, there is a well pronounced pattern between Force and Deflection parameters in the linear part of the Force vs. Deflection curve, and based on this, we proposed a linear regression model between logarithm values of the force percentage (in relation to the rupture) and the denominator of the span value (as a Deflection parameter), resulting R2 equal to 97.41%. This result makes the conduction of the static bending test easier in specialized laboratories for testing of wood.